2009
DOI: 10.1007/978-1-60761-198-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Motility In Vivo Using Zebrafish

Abstract: Zebrafish have emerged as a powerful model organism to study neutrophil chemotaxis and inflammation in vivo. Studies of neutrophil chemotaxis in animal models have previously been hampered both by the limited number of specimens available for analysis and by the need for invasive procedures to perform intravital microscopy. Due to the transparency and cell permeability of zebrafish embryos these limitations are circumvented, and the zebrafish system is amenable to both live time-lapse imaging of neutrophil che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…In view of this, we first addressed the expression of both zebrafish cxcl8 at different time points in 3 dpf Tg(mpx:gfp)i114 larvae under acute inflammatory conditions using quantitative PCR (qPCR). In this study, we made use of the tail fin transection model, a validated model to investigate acute inflammation (16)(17)(18)(19)(20)(21)(22)(23). We found that the mRNA levels of cxcl8-l1 and cxcl8-l2 were significantly increased in injured tail fin tissue and peaked at 1 hpw (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In view of this, we first addressed the expression of both zebrafish cxcl8 at different time points in 3 dpf Tg(mpx:gfp)i114 larvae under acute inflammatory conditions using quantitative PCR (qPCR). In this study, we made use of the tail fin transection model, a validated model to investigate acute inflammation (16)(17)(18)(19)(20)(21)(22)(23). We found that the mRNA levels of cxcl8-l1 and cxcl8-l2 were significantly increased in injured tail fin tissue and peaked at 1 hpw (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, the optical transparency of zebrafish and the development of fluorescent cell-specific transgenic lines have enabled the in vivo study of leukocyte biology (14,15). Zebrafish neutrophils have now been extensively studied in inflammation (16)(17)(18)(19)(20)(21)(22)(23), infection (24)(25)(26)(27), and tumor progression (28)(29)(30).…”
mentioning
confidence: 99%
“…The power of the zebrafish model lies in its suitability for genetic approaches, high-throughput screening, and live imaging studies. Fluorophore-marked transgenic lines are now available that allow unprecedented visualization of pathogen interactions with macrophages and neutrophils, the major phagocytic innate immune cell types of zebrafish larvae [711]. As early as one day after fertilization (dpf), zebrafish embryos display phagocytic activity towards microbial infections [12] and are able to mount an innate immune response with a transcriptional signature that resembles responses in mammalian or cell culture systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…We also discuss zebrafish models of human immunodeficiency that have provided new insight into leukocyte migration during development and disease. Details of the ontogeny of zebrafish early immune cells and established tools for live-cell imaging in zebrafish have been reviewed elsewhere Mathias et al, 2009a) and will therefore not be covered here.…”
Section: Introductionmentioning
confidence: 99%